Notes for an Eulogy on the Finiteness of the Human Condition - Fornet-Betancourt, Raúl (Concilium, 2021)
Under the generic titles of "posthumanism" and/or "transhumanism" we can presently see widening currents of thought claiming to represent new approaches that go beyond the traditional sense of humanist thinking. While there is no intent to deny the novelty of the challenges represented by such approaches when understanding the human condition, and which can be evidenced, for example through the application of their techniques for the "betterment" of "human material", this article sees these currents alongside one of man's oldest dreams: the achievement of immortality. Against this background we shall argue for the permanence and relevance of man's mortality.